Новооткрытые рукописи коми-пермяцкого словаря Ф. А. Волегова [Newly Discovered Manuscripts of the Komi-Permyak Dictionary by F. A. Volegov] - Roman Gaidamashko; Alexander Levichkin (Linguistica Uralica)
In the collections of the Russian State Library and the Russian National Library, two hand-written Komi-Permyak dictionaries were found, which were not previously mentioned in the scientific literature. According to preliminary data, the newly discovered manuscripts are versions of the Russian-Permyak dictionary by Fedot AleksejeviÄ Volegov (1790â1856). The dictionary of F. A. Volegov is known due to the publication of a handwritten copy from the Antal Reguly collection, carried out by Károly Rédei (1968). This article presents: the biography of F. A. Volegov and some data about his Russian-Permyak dictionary; a brief archaeographic description of both newly discovered manuscripts; preliminary textological observations on the relationship of these two manuscripts with already known handwritten copies of the Russian-Permyak dictionary by F. A. Volegov.